New Monoterpenes, Diterpenes, and Lignans from Abies recurvata - Li, Yong-Li; Zhang, Ji-Gang; Yu, Ping; Ke, Bei-Lei; Ye, Ji; Yang, Xian-Wen; Jin, Hui-Zi; Zhang, Wei-Dong (Planta Medica, 2012)
From the aerial part of Abies recurvata, 62 miscellaneous chemical constituents were isolated including 6 new and 56 known ones. The new compounds comprised three monoterpenes, two diterpenes, and one lignan. Their chemical structures were characterized on the basis of various spectroscopic techniques. Dihydrodehydrodiconiferyl alcohol (35) showed the strongest inhibitory effects against lipopolysaccharide-induced nitric oxide production in RAW 264.7 cells with an IC50 value of 66.4 µM.
Keywords: Abies recurvate; Pinaceae; monoterpenes; diterpenes; lignin; nitric oxide; lipopolysaccharide